Spectral interference elimination and self-absorption reduction in laser-induced breakdown spectroscopy assisted with laser-stimulated absorption. (November 2020) - Tang, Yun; Ma, Shixiang; Yuan, Rui; Ma, Yuyang; Sheng, Wei; Zhan, Shiping; Wang, Junnian; Guo, Lianbo
Highlights: LIBS assisted with laser-stimulated absorption (LSA-LIBS) was proposed to reduce self-absorption in the presence of spectral interference. Rational selection of the excitation line was proved to be an important factor for self-absorption reduction. The self-absorption factor of the Ni I 341.47 nm line was reduced by 85% using LSA-LIBS. Abstract: Spectral interference and self-absorption seriously affect the accuracy of quantitative analysis in laser-induced breakdown spectroscopy (LIBS). In this work, we used LIBS assisted with laser-stimulated absorption (LSA-LIBS) to solve these problems. Taking nickel (Ni) in the alloy structural steel as an example, the results show that the spectral interference of Ni lines was eliminated, the self-absorption factor of the Ni I 341.47 nm line was reduced by 85%, and the average relative error for determination of Ni element was reduced by 83% using LSA-LIBS. The results indicate that spectral interference and self-absorption can be reduced simultaneously in LSA-LIBS.